THE UNIVERSITY AS A SPACE FOR INTERVENTION IN PROFESSIONAL ORIENTATION: ONE EXPERIENCE AT THE UNIVERSIDAD PERUANA DE CIENCIAS APLICADAS (UPC) - Navarrete Talavera, Patricia (2007)
The present article constitutes a reflection about the University as a space for intervention in vocational and professional orientation, taking into account the work presently done as well as the actual theoretical discussions and taking as a reference the experiences that are being developed at the Peruvian University of Applied Sciences nowadays. Professional orientation is conceived as the meaning and importance that the vocational development of a person has, understanding that this does not necessarily corresponds to one moment in your life, but that it develops in a permanent manner during your entire life cycle. Given that, in the world that we live in, the generation of knowledge and the demands for training are continuous, orientation takes a primordial role in the professional formation of the students and thus, in the University’s system that shelters us too. Therefore, it becomes necessary to generate new job offers that contemplate jointly: the educational model, the professors’ job, the services of the jobs that are available and the Orientation Area.